2004
DOI: 10.1300/j013v39n04_03
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Behaviors and Cancer Screening of Lesbians: Results of the Boston Lesbian Health Project II

Abstract: This paper reports data on health related behaviors and cancer screening from the Boston Lesbian Health Project II (BLHP II), a replication of a national survey of lesbians on a variety of health-related variables completed in 1987. The findings suggest that lesbians have increased their use of primary care, including routine physical examinations, pap smear screening for cervical cancer, and mammography for breast cancer, but that rates continue to be lower than would be expected for women in general. Younger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 34 publications
1
37
1
Order By: Relevance
“…Alternatively, there may fewer opportunities for lesbians to be referred to substance abuse treatment, in part, because they may be less likely than heterosexual women to visit primary care providers on a regular basis. 46 In contrast to findings from some population-based studies in which bisexual women have shown higher rates of substance use and other mental health problems, 47,48 the bisexual women in this study were similar to the lesbians in most of the outcomes assessed. This divergence in findings may be due to differences in sampling and recruitment procedures.…”
Section: Discussioncontrasting
confidence: 99%
“…Alternatively, there may fewer opportunities for lesbians to be referred to substance abuse treatment, in part, because they may be less likely than heterosexual women to visit primary care providers on a regular basis. 46 In contrast to findings from some population-based studies in which bisexual women have shown higher rates of substance use and other mental health problems, 47,48 the bisexual women in this study were similar to the lesbians in most of the outcomes assessed. This divergence in findings may be due to differences in sampling and recruitment procedures.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous population-based studies found women who identified as lesbian to be less likely to have had a Pap test than those who identified as heterosexual. [14][15][16] All of these studies, however, examined health care utilization among women who identified as lesbians; none looked at behavior.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37] Primary mental health concerns reported by lesbian women include depression, anxiety and panic disorders, alcoholism, eating disorders, and suicide attempts. 38 Among LGBT individuals, poor mental health has been associated with poor health behaviors such as illicit drug use, 39,40 tobacco use, [41][42][43] and alcohol abuse. 12 Additionally, among sexual minority women, higher depression and anxiety have been associated with poor health-related quality of life, 44 lack of exercise, 12 obesity, and poor general health.…”
Section: Introductionmentioning
confidence: 99%